Nephrolithiasis and it’s Management with Homoeopathy (Homoeopathy for All, 2024)
Crystal agglomerates that grow in the  urinary tract and can occasionally pass  through it cause a frequent urological  condition known as kidney stones (KS).  Greek term nephros means kidney,  uro means urinary and lithos means  stone, are also used to refer to it as  nephrolithiasis or urolithiasis.  In other system of medicine, there are  various methods of treatment including  surgery with chances of recurrence. Hence, there is a need to develop  a simple cost effective, painless line  of treatment, which not only removes  the calculi/ calculi’s, but also helps in  removing the tendency for recurrence of  calculi formation. Homoeopathy offers  good number of remedies for removing  calculi and tendency for recurrence of  calculi. Now a day’s homoeopathy is  playing a crucial role in the management  of renal calculi and this helping in  treating the problem without surgery  and in avoiding recurrence of the disease  with the use of homoeopathic medicine.
Keywords: Homeopathy; Nephrolithia sis; stone; Renal colic; Surgical Disease